Crosstalk reduction through wavelength assignment in WDM photonic switching networks. - Tak-Shing Wong (IEEE Transactions on communications)
As the deployment of wavelength-division multiplexing (WDM) transmission facilities speeds up, the next step is to add cross-connects to route WDM signals. Electro-optical directional couplers (DCs) are well suited for the task since they can pass WDM signals. However, DCs suffer an intrinsic crosstalk problem. Removing crosstalk has been an important design issue. In this paper, we show how to take advantage of the multiple-wavelength characteristic of a WDM signal to reduce crosstalk in a DC-based photonic switching system